Quality of life after colorectal cancer surgery in patients from University Clinical Hospital Mostar, Bosnia and Herzegovina - Trninić, Zoran (Array, 2009)
Summary: Quality of life (QoL) has become an important outcome measure for patients with cancer, but results from population-based studies are infrequently published. The objective of this study was to asses QoL in patients who underwent the colorectal cancer (CRC) surgery and to compare it to the QoL of general population. The patients who were admitted from January 2004 until May 2006 at the Department of Gastrointestinal Surgery at the Clinical Hospital Mostar, Bosnia and Herzegovina were divided in three groups: group of CRC patients who had received surgery and as a result of surgical treatment have colostomy, group of CRC patients who had received surgery in the same period and don’t have colostomy and the third group that consisted of controls. QLQ-C30 and QLQ-CR38 questionnaires by the European Organization for Cancer Research and Treatment (EORTC) were used. A total of 67 patients were included in this study, supplemented by the thirty healthy examinees. Healthy group had significantly better results in physical functioning compared with colorectal cancer patients and better results in cognitive and social functioning. Also, they reported symptoms of diarrhea and constipation less frequently than the group with colostomy and. The group with colostomy had poorer results in emotional functioning than the group without colostomy, and also reported significantly poorer results for domain »body image«. Healthy group showed better results in sexual enjoinment than the patient with colorectal cancer. Patients without colostomy reported more micturition and defecation problems and female sexual problems compared to the healthy group. Generally we found that healthy population had better results than the CRC patients, while the patients with stoma had worse results than the nonstoma patients. The results presented here suggest that psychological treatment should be an integral part of the CRC treatment plan